Sprawność fizyczna żołnierzy z województwa Zachodniopomorskiego = Physical fitness of soldiers from the province of Zachodniopomorskie - Stankiewicz, Błażej Stanisław; Bożek, Radosław (Journal of Education, Health and Sport, 2016)
Stankiewicz Błażej, Bożek Radosław. Sprawność fizyczna żołnierzy z województwa Zachodniopomorskiego = Physical fitness of soldiers from the province of Zachodniopomorskie. Journal of Education, Health and Sport. 2016;6(12):184-214. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.193030 http://ojs.ukw.edu.pl/index.php/johs/article/view/4045 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 06.12.2016. Sprawność fizyczna żołnierzy z województwa Zachodniopomorskiego Physical fitness of soldiers from the province of Zachodniopomorskie Błażej Stankiewicz¹, Radosław Bożek¹ Blazej Stankiewicz¹, Radoslaw Bozek¹ ¹ Uniwersytet Kazimierza Wielkiego w Bydgoszczy ¹ Kazimierz Wielki University in Bydgoszcz Słowa kluczowe: sprawność fizyczna, Wojsko Polskie, armia Key words: physical fitness, the Polish Army, army Streszczenie Celem pracy było poznanie poziomu sprawności żołnierzy 100 Batalionu Łączności. W sprawdzianie sprawności fizycznej udział wzięło 403 żołnierzy. W grupie tej znalazło się 15 oficerów, 203 podoficerów i 185 szeregowych. W ramach sprawdzianu żołnierze poddani zostali czterem próbom: podciągania na drążku, skłony tułowia w czasie 2 minut, bieg wahadłowy 10x10 metrów oraz marszobieg na 3000 metrów. Z przeprowadzonych badań wynika, że największym poziomem sprawności fizycznej wykazali oficerowie, którzy uzyskali największą ilość ocen bardzo dobrych we wszystkich czterech próbach. Natomiast najniższym poziomem sprawności fizycznej wykazali szeregowi. Badani żołnierze najlepsze wyniki uzyskali podczas wykonywania skłonów tułowia w czasie 2 minut. Natomiast najgorsze wyniki badani żołnierze uzyskali podczas marszobiegu na 3000 metrów, co świadczy o niskim poziomie wytrzymałości. Zróżnicowanie ocen wewnątrz poszczególnych grup wiekowych, występujące we wszystkich trzech korpusach, udowodniło, że wiek badanych żołnierzy i wiążące się z nim normy wymagań nie wpływają na osiągane rezultaty. Summary The aim of the study was to determine the fitness level of troops of 100 Battalion of Communications. The quiz physical attended by 403 soldiers. In this group, there were 15 officers, 203 non-commissioned officers and 185 privates. As part of the test soldiers were subjected to four tests: pull on the stick, the body slopes in 2 minutes, running swinging 10x10 meters and run at 3,000 meters. The study shows that the greatest level of physical fitness showed officers, who obtained the greatest number of very good grades in all four trials. In contrast, the lowest level of physical fitness showed a number. Respondents soldiers the best results obtained during the execution of the torso bends 2 minutes. While the worst performing subjects soldiers received during the slow-run 3000 meters, which indicates a low level of strength. Differentiation of ratings within each age group, present in all three bodies, proved that the age of the respondents soldiers and binding with it the standard requirements do not affect the achieved results.